1994
DOI: 10.1136/jech.48.5.490
|View full text |Cite
|
Sign up to set email alerts
|

School injuries in Athens: socioeconomic and family risk factors.

Abstract: The distribution of information on fractures in responding urban and rural probands. Both sexes from each area are grouped tcgether The percentage offractures from each source of information is given. a forgotten fracture. This means that all studies on fracture prevalence must be based on some kind of fracture documentation rather than proband memory only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…In a rural region of China, a general inverse association was reported between education level and dyslipidemia 10 . Similar data were observed with Greek adolescents 14 . Also, evaluating the Greek participants of the EPIC Study, Benetou et al observed that total blood cholesterol was inversely related to education level in both men and women.…”
Section: Discussionsupporting
confidence: 89%
“…In a rural region of China, a general inverse association was reported between education level and dyslipidemia 10 . Similar data were observed with Greek adolescents 14 . Also, evaluating the Greek participants of the EPIC Study, Benetou et al observed that total blood cholesterol was inversely related to education level in both men and women.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have already shown the incidence of child injury and the incidence of child pedestrian accidents to be associated with factors including social class and income deprivation (Preston, 1972;Braddock et al, 1991;Roberts and Power, 1996;Roberts, 1997;LaScala et al, 2004;Laflamme et al, 2009); family circumstance, such as single parenthood and low levels of parental education (Bergstrom and Bjornstig, 1991;Judge and Benzeval, 1993;Petridou et al, 1994); ethnicity (Lawson and Edwards, 1991;Christie, 1995;Howard et al, 2005); and conditions of the physical environment, particularly those characteristic of urbanised localities (Bagley, 1992;Petch and Henson, 2000;Mayr et al, 2003;Dissanayake et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, there is considerable evidence of inequalities in childhood injury risks across social groups. [3][4][5][6][7][8][9][10][11][12] In addition, there is little literature concerning how socioeconomic patterns vary at different ages during childhood and adolescence, as most previous studies have dealt with rather wide age categories. Likewise, possible variations by injury groups with increasing age are rarely addressed.…”
mentioning
confidence: 99%